Pemetaan Tingkat Kebutuhan Bahasa Inggris di Destinasi Wisata Kabupaten Halmahera Barat - Halida Nuria; Indra Purnawan Panjaitan (Universitas Khairun, 2022)
This research focuses on mapping the English needs in West Halmahera. The background for choosing the title is because there are several tourist attractions that are excellent in West Halmahera, namely Lapasi Beach, Gamtala Mangrove tourism, and Tanjung Rappapelangi Bubanehena. The three attractions mentioned above are managed by the community. The community as tourism actors in these places must be ready and have knowledge of their tourism awareness. In addition to tourism-conscious knowledge, language as a means of communication is important between guests and hosts. Guests are tourists who come to tourist objects and the hosts are people who manage tourism objects in West Halmahera Regency. Language is an important thing in the world of tourism services and more specifically English. Not being a stranger, almost all over the world make English a very effective communication tool for the smooth running of a goal. The purpose of this study is to find out the mapping of the level of English language needs in West Halmahera Tourism Destinations. The type of this research uses descriptive qualitative methods, namely the data is described through words. The description of this elaboration is through data on the need for English in the community as tourism actors in West Halmahera Tourism Objects. In this case the research subject is the community as a tourism manager. The focus of the research location is on three tourist attractions, namely Lapasi Beach, Gamtala Mangrove tourism, and Tanjung Rappapelangi Bubanehena. The result of the research is that the attractions of Lapasi Beach, Gamtala Mangrove, and Tanjung Rappapelangi have the potential for beautiful marine tourism objects, nature tourism, historical tourism, and cultural tourism. Can be categorized how to manage well by the manager / community. In mapping the need for English in tourist attractions in West Halmahera, there are three tourist objects that really need English learning. This is due to the low knowledge of English owned by the manager/community. This statement is also supported by the findings of this study, namely, first, the needs of the community/manager for knowledge of English can help self-actualization. Second, the community realizes the importance of the role of English in supporting the development of tourism objects, and the third is the community's desire to learn English through training for self-development. Keywords : Mapping, Needs, English, West Halmahera